Investigations on Multilayered TCO as Transparent Electrode in Organic Devices. Issue 1 (November 2015) - Sharma, Vikas; Meena, Pooja; Salim, Amena; Vyas, Rishi; Sachdev, K.
Summary: A sandwiched structure with a metal layer embedded between two metal oxide layers was fabricated on glass substrate to be used as transparent electrode in organic devices. The oxide layers of ZnO were dip coated with a thickness of about 60 nm each while the metal inter layer was sputter coated with a thickness of about 5 nm at room temperature. The deposited films were annealed at 200°C for 2 hrs to remove all additives. Such structures have been found to be suitable for applications in organic solar cell and OLED. The samples have been characterized using XRD, SEM and EDAX. Optical properties were measured by UV‐VIS and AFM was used to measure the roughness. The XRD pattern indicates the nearly amorphous structure of the thin film. The size of the aggregates as given by FESEM ranges from 30–50 nm and EDAX confirms the presence of elements of the three layers. The roughness as calculated using AFM is about 2.40 nm. UV‐VIS spectroscopy showed a high transparency of over 87% in the visible region for the sandwich structure making it suitable for TCO applications.